The Introduced Fanworm, Sabella spallanzanii, Alters Soft Sediment Macrofauna and Bacterial Communities - Atalah, Javier; Floerl, Oliver; Pochon, Xavier; Townsend, Michael; Tait, Leigh; Lohrer, Andrew M. (Frontiers in Ecology and Evolution, 2019)
The Mediterranean fanworm, Sabella spallanzanii, is an introduced and established “unwanted species” in New Zealand, subject to nationwide targeted surveillance in port, marina, urban and natural environments. S. spallanzanii has the potential to change soft-sediment benthic habitats due to the physical presence of the fanworm’s tube and associated biological activities, particularly suspension feeding and bio-deposition. A 6-month field experiment was conducted to investigate the impacts of S. spallanzanii on existing communities within invaded soft-sediment habitats. Macrofaunal communities were assessed using traditional sampling and taxonomy while microbial and eukaryotic communities were characterised using metabarcoding of 16S and 18S ribosomal genes, respectively. Live and mimic S. spallanzanii were transplanted at different densities (10 - 50 individuals per m2) into experimental plots with existing assemblages, to test for potential biological and/or physical effects on benthic communities. Analyses revealed consistent, significant differences in macrofaunal, eukaryote and bacterial assemblages in the presence of live S. spallanzanii and mimics, indicating that these effects are brought about by biological and physical functions associated with the worms. The presence of S. spallanzanii did not alter total abundance and taxa richness of benthic assemblages but resulted in compositional differences. Changes in the structure of native benthic communities, as indicate by this study, can potentially impact functioning of soft-sediment habitats, through alterations to nutrient cycling, bioturbation and benthic-pelagic coupling. Quantitative measurements of impacts are crucial to understand the trajectory of marine invasions, their roles in re-structuring communities, and to guide management efforts.